Chronic neuroinflammation impairs waste clearance in the rat brain - Swathi Suresh; Jacob Larson; Jacob Larson; Kenneth Allen Jenrow; Kenneth Allen Jenrow (Frontiers Media S.A., 2022)
BackgroundPrevious reports have established an association between impaired clearance of macromolecular waste from the brain parenchyma and a variety of brain insults for which chronic neuroinflammation is a common pathological feature. Here we investigate whether chronic neuroinflammation is sufficient to impair macromolecular waste clearance from the rat brain.MethodsUsing a rodent model of chronic neuroinflammation induced by a single high-dose injection of lipopolysaccharide, the clearance kinetics of two fluorophore-conjugated dextran tracers were assayed at 8-weeks post-induction. The expression and distribution of amyloid β and aquaporin-4 proteins within selected brain regions were assayed at 36-weeks post-induction, following open-field, novel object recognition, and contextual fear conditioning assays.ResultsChronic neuroinflammation significantly impaired the clearance kinetics of both dextran tracers and resulted in significantly elevated levels of amyloid β within the hippocampus. Aquaporin-4 density on astrocytic endfeet processes was also reduced within multiple brain regions. These pathologies were associated with significantly enhanced contextual fear memory.ConclusionOur results suggest that chronic neuroinflammation is sufficient to compromise the clearance of macromolecular waste from the brain parenchyma and may be the root cause of impaired waste clearance associated with a variety of brain pathologies.